Phytochemical Contents of Underutilized Edible Plant from Riau Province, Ridan (Nephelium maingayi Hiern Ã¢â¬â Sapindaceae) - Nery Sofiyanti; Mayta Novaliza Isda; Fitmawati Fitmawati; Asih Rahayu Ajeng Agesti; Ikhwan Taufik; Maya Sari; syafroni Pranata (Jurnal Biologi Tropis, 2021)
Ridan (Nephelium maingayi) is one of Nephelium (Sapindaceae) member distributed in Riau Province. This underutilized edible plant is commonly found as wild species, and poses three different fruit morphologies (oval, asymmetric and rounded shaped fruit). The phytochemical contents of these fruit species had not been reported. This study aimed to identify the phytochemical contents of fruit parts (peel, aril and seed) of three different fruit shapes of N. maingayi (oval, asymmetric and rounded shaped fruit) from Riau Province. A total of six secondary metabolite groups were tested (alkaloid, terpenoid, steroid, flavonoid, saponin dan tannin), using qualitative analysis based on the presence of precipitation (alkaloid), the change of mixture color (steroid, terpenoid, flavonoid and tannin) and soapy foaming substance for saponin. The result showed that peels of Ridan (N. maingayi) gave the highest phytochemical contents (alkaloid, terpenoid, flavonoid, saponin and tannin.). Terpenoid and saponin were found in peel, aril and seed of three different fruit shapes. This study concluded that the phytochemical contents of three fruit shapes of Ridan (N. maingayi) varies among the different shapes of fruit. This result of this study provide the first information of bioactive profile of N. maingayi form Riau Province.